Pengaruh Profitabilitas, Leverage Dan Ukuran Perusahaan Terhadap Penghindaran Pajak Perusahaan Sektor Kesehatan Yang Terdaftar Di BEI - Cahyasari, Monika Weni; As’ari, Hasim (Politeknik Negeri Ambon, 2024)
Obligatory contribution to the internal state in the form of a fixed payment, from both individuals and corporations, is the definition of tax which functions as state revenue. However, the obligation to pay taxes can reduce a company's profits, thus triggering efforts to avoid tax obligations. The aim of this research is to examine various aspects that may influence a company's tendency to engage in tax avoidance. This quantitative research employs purposive sampling in data collection. The findings show that profitability has a significant influence impact on tax avoidance behavior, while benefit and company size do not exhibit an important influence.